Development of a Test for Evaluating Beginning Taekwondo Students’ Motor Skills - Pieter, Willy; Heijmans, John (Revista de Artes Marciales Asiáticas, 2012)
The purpose of the present investigation was to develop a motor skills test for beginners in tae-kwondo. Subjects were students enrolled in a beginning taekwondo class at a university on the West Coast of the USA. The taekwondo skills test battery was based on previous work in gymnastics and wrestling. Test-retest reliability, i.e., repeatability of the test, and objectivity coefficients, i.e., an index of the consistency between the raters, were calculated. The objectivity, i.e., a measure of the consistency between the raters over both days for Group 1 was very high, and for Group 2, high. The reliability, or the consistency of the results of the test when administered on two different occasions, was very high for both groups. Future research should comprise more subjects, while test batteries for intermediate and advanced students should be developed.